OPTIMIZATION OF E-COMMERCE FOR USED COOKING OIL AQUADES TO SUPPORT THE GREEN ECONOMY AND UMKM DIGITALIZATION - Silalahi, Flora Elisabeth; Ekawulandari, Sri; Mendrofa, Putri; Ledewick, Ledewick (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to optimize the use of e-commerce in marketing aquades products made from used cooking oil developed by UFLO Beauty and to examine its role in supporting the green economy and MSME digitalization. The research applied a mixed-method approach by combining qualitative interviews with company management and quantitative surveys of 100 respondents. The findings show that 74% of respondents are aware of the economic value of used cooking oil, 87% support the concept of the green economy, and 98% emphasize the need for MSME digitalization training. Furthermore, 70% of respondents believe that e-commerce has great potential to strengthen product marketing, although challenges remain in digital literacy, SEO optimization, and infrastructure. The study concludes that e-commerce is an effective platform to expand market reach, improve competitiveness, and promote environmentally friendly business practices that contribute to the green economy. Keywords: e-commerce; sublimation; used cooking oil; aquades; green economy. Abstrak: Penelitian ini bertujuan untuk mengoptimalkan penggunaan e-commerce dalam pemasaran produk aquades berbahan dasar minyak jelantah yang dikembangkan oleh UFLO Beauty serta menganalisis perannya dalam mendukung ekonomi hijau dan digitalisasi UMKM. Metode penelitian menggunakan pendekatan campuran (mixed-method) dengan menggabungkan wawancara kualitatif bersama manajemen perusahaan dan survei kuantitatif terhadap 100 responden. Hasil penelitian menunjukkan bahwa 74% responden mengetahui nilai ekonomi minyak jelantah, 87% mendukung konsep ekonomi hijau, dan 98% menyatakan perlunya pelatihan digitalisasi bagi UMKM. Selain itu, 70% responden menilai e-commerce berpotensi besar dalam meningkatkan pemasaran produk, meskipun masih terdapat kendala literasi digital, optimasi SEO, dan keterbatasan infrastruktur. Penelitian ini menyimpulkan bahwa e-commerce merupakan platform yang efektif untuk memperluas jangkauan pasar, meningkatkan daya saing, serta mendorong praktik bisnis ramah lingkungan yang berkontribusi terhadap ekonomi hijau. Kata Kunci: e-commerce; sublimasi; minyak jelantah; aquades; ekonomi hijau.